Vına Sebelum 7 Harı: Netızen Behavıor And Socıal Medıa News Reportıng - Wiby Bagaskara; Ramizar Hamka; Mukarto Siwoyo; Dedet Erawati (Cita Konsultindo Research Center, 2024)
Social media now plays an important role in the change and innovation of human life because of the efficient and flexible online dissemination of information. The Vina Cirebon murder case is back in the public spotlight after the movie titled Vina Sebelum 7 Hari has been released in theaters. After this case rose again, many social media accounts were competing to provide information updates both about the film and about the development of the case. the purpose of this study is to determine the extent to which the framing made by the media has an effect on the behavior and assessment of netizens on a reported event. The research method used in social media reporting is Robert N. Entman's media framing analysis and qualitative methods. The results of this study show: (1) define the problem in the news issue brings pro value in the Vina Cirebon murder case raised in the film Vina Before 7 Days as the alleged perpetrator of the murder; (2) diagnose causes tend to accentuate the context of the facts revealed by the family visited by 2 mysterious men to stop filming; (3) make moral judgement, namely clarification of the victim's family who were visited by 2 mysterious men to stop a film as a threat; (4) treatment recommendation by emphasizing the allegation that the 2 mysterious men who came to the victim's family were the perpetrators in the Vina Cirebon murder case.